2013
DOI: 10.1386/stap.33.2.133_1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring radical openness: A porous model for relational festival performance

Abstract: Popular music festivals are convivial spaces where paradigms of play and participation proliferate. 'Exploring radical openness' investigates the concept of relational performance where encounter and dynamic exchange are prioritized. Drawing on extensive practice-led research conducted predominantly within the UK festival circuit, it provides a model for interactivity that not only acknowledges the inherent unpredictability of festival sites but also exploits it in the pursuit of inclusivity and radical openne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The Kelston African group, for example, acknowledged this approach, 'offering moves from Nigeria, Ghana, Congo and South Africa [wanting] to show the strength of our solidarity'. The inventiveness of these practices confirmed the strength of cross-cultural friendships and collective worldviews (Faleolo, 2020), but also how festivals provided an openness for such cross-cultural possibilities (O'Grady, 2013a). Youth participants also picked up on the extent of this cultural diversity at festivals stating that it encouraged cross cultural mixing: 'it's so diverse, that you can just…meet new people, you know, see people you know.…”
Section: Trans-ethnic Solidaritiesmentioning
confidence: 79%
“…The Kelston African group, for example, acknowledged this approach, 'offering moves from Nigeria, Ghana, Congo and South Africa [wanting] to show the strength of our solidarity'. The inventiveness of these practices confirmed the strength of cross-cultural friendships and collective worldviews (Faleolo, 2020), but also how festivals provided an openness for such cross-cultural possibilities (O'Grady, 2013a). Youth participants also picked up on the extent of this cultural diversity at festivals stating that it encouraged cross cultural mixing: 'it's so diverse, that you can just…meet new people, you know, see people you know.…”
Section: Trans-ethnic Solidaritiesmentioning
confidence: 79%
“…The framework of liminality lends itself well to the analysis of festivals (O'Grady, 2013a(O'Grady, , 2013b) and it links with notions such as third space, which is understood as liminal as well (Bhabha, 1996). Festivals consist of an interruption, or discontinuum of the daily flows of life through their performative and ritualistic features.…”
Section: Festival Spacementioning
confidence: 99%
“…In recent years, research has identified festivals as sites where diverse communities can articulate identities, form solidarities, and resist mainstream narratives towards their respective cultures (Bramadat, 2001;Lee, Arcodia, & Lee, 2012a, b). Due to the liminal nature of these festivals, they can often constitute spaces of highly public affirmation of these cultural identities (O'Grady, 2013a). O'Grady (2013a) suggests such sites also create a radical openness, that can enable a bridging across cultural divides and disrupt hierarchies established in day-to-day interactions.…”
Section: Context and Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, research has identified festivals as sites where diverse communities can articulate identities, form solidarities, and resist mainstream narratives towards their respective cultures (Bramadat, 2001;Lee, Arcodia, & Lee, 2012a, b). Due to the liminal nature of these festivals, they can often constitute spaces of highly public affirmation of these cultural identities (O'Grady, 2013a). O'Grady (2013a) suggests such sites also create a radical openness, that can enable a bridging across cultural divides and disrupt hierarchies established in day-to-day interactions.…”
Section: Context and Aimsmentioning
confidence: 99%